Spontaneous occlusion of a traumatic false aneurysm of the peroneal artery - Kocakoc, E; Bozgeyik, Z; Ozgocmen, S; Ozdemir, H (Wiley, 2003)
false aneurysm can occur after either open or closed injury of the arterial wall. Hemorrhage becomes confined within fascial compartments, resulting in a hematoma.(1) The pathogenesis of the false aneurysm is characterized by disruption of arterial continuity with extravasation of blood into surrounding tissues.' Pseudoaneurysms of the lower extremity arteries occur as a result of trauma or iatrogenic injury of the arterial wall.(3,4) In years past, pseudoaneurysms were encountered as common complications of bacterial endocarditis when effective antibacterial treatment was not available, but today, they occur almost exclusively in people using intravenous drugs.(5) In addition, it is also necessary to consider the risk of false aneurysm formation in contiguous wound infection.(2) A pseudoaneurysm may cause complications, including pain, rupture, bleeding, infection, peripheral embolization, and deep venous thrombosis due to venous compression.(3) We report the case of a false aneurysm of the peroneal artery that underwent spontaneous occlusion.
Keywords: Tibial Artery; Pseudoaneurysm; Complication; Ankle